EDUKASI PENGENALAN BUDIDAYA SAYURAN KEPADA SISWA SEBAGAI INOVASI MUATAN LOKAL DI SEKOLAH DASAR - Dessy Mega Harumawati; Heru Subrata; Ari Metalin Ika Puspita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Vegetables are a source of nutrients that are important for body health and have a vital role in fulfilling daily nutritional needs. Based on data from Basic Health Research in 2018, children with the age group ranging from 5-9 years old have a proportion that consumes less vegetables and fruit, as much of 96.9%. From this data, only 3.1% consume more than 5 portions of vegetables a week. In fact, the Indonesian population is categorized as consuming enough vegetables and fruit if they consume at least 5 portions a week. Many factors cause this condition, one of them is a lack of knowledge about vegetables. Education on vegetable cultivation is a solution to this problem. This research is a type of qualitative research. The result of this research shows that education and practice of vegetables cultivation have positive values and perceptions for students. This directly contributes on increasing students' learning interest and motivation in honing their self-reliance and life skills.